The Role of Agritourism’s Impact on the Local Community in a Transitional Society: A Report From Serbia - Marko D. PETROVIĆ; Ivana BLEŠIĆ; Aleksandra VUJKO; Tamara GAJIĆ (Transylvanian Review of Administrative Sciences, 2017)
This study assessed local residents’ attitudesin Serbia toward the impact of agritourismin their surroundings, using a Tourism ImpactAttitude Scale (TIAS). Till now, analysis of theimpact of tourism on the attitudes of residentsin rural areas of Serbia and other Balkan transitionalcountries is insuffi ciently researched. Theanalyzed items of the TIAS were grouped intofour factors: personal and community benefi ts(grouped eight items); negative impacts (sevenitems); concern for the local tourism development(fi ve items); and general opinion abouttourism development (three items). The factorsexplain 47.47% of the variance. Furthermore,the results showed that residents consider thepossibility to have more money to spend as themost important impact of tourism development. Itis followed by the support of local authorities topromote tourism development. The third relevantissue for the residents is related with encouragementof tourism in the local community. Theseare the key propositions to start an initiative forthe local communities to actively participate inagritourism development. The results provideresidents, tourism organizers and local authoritieswith important community perceptions pertainingto the agritourism’s impact.